A correlation study of the relationship between flat foot with anterior pelvic tilt and sacroiliac joints dysfunction among undergraduate students - Tan, Bee Thong (2022)
Background: Flat foot is a common observed clinical foot.The medial longitudinal arch becomes flatter or absence among the flat foot individuals. As the foot mechanic altered, it might affect the alignment of lower limbs up to pelvis. It led to medial rotation of hip and knee, and subsequently cause anterior pelvic tilt. The excessive forward rotation of pelvic might place more load over the sacroiliac joints and cause pain and dysfunction. The purpose of conducting this research is to determine the relationship between flat foot with anterior pelvic tilt and sacroiliac joints among undergraduate students. Methods: Screening booth was built in UTAR, Sungai Long Campus. The undergraduate students with unilateral or bilateral flat foot were recruited in this study. The CSI, tri-goniometirc method, Shimpi Prone SIJ test were used to assess the flat foot, degree of anterior pelvic tilt, and sacroiliac joints dysfunction. Results: There were 98 participants in total diagnosed with flat foot deformity. There was 55.7% of prevalent of flat foot deformity among undergraduate students. There was only fair and positive significant difference was found between anterior pelvic tilt and sacroiliac joints dysfunction among third degree of flat foot participants (r=0.555, p=0.009). Conclusion: Majority of severe form of flat foot subjects were found with higher BMI index and diagnosed bilaterally. In addition, the relationship between anterior pelvic tilt and sacroiliac joints dysfunction only occurred among the flat foot subjects with more severe degree.